Smooth Muscle Tumor of Uncertain Malignant Potential (STUMP): A Comprehensive Multidisciplinary Update - Andrea Tinelli; Ottavia D’Oria; Emanuela Civino; Andrea Morciano; Atif Ali Hashmi; Giorgio Maria Baldini; Radomir Stefanovic; Antonio Malvasi; Giovanni Pecorella (Medicina, 2023)
Background and Objectives: The uterine smooth muscle tumors of uncertain malignant potential (STUMP) are tumors with pathological characteristics similar to leiomyosarcoma, but that do not satisfy histological criteria for leiomyoma. These are problematic lesions with intermediate morphologic features; thus, diagnosis and treatment are difficult. This narrative review aims to review data in the literature about STUMPs, particularly focusing on management and therapeutic options and strategies for women who desire to preserve fertility. Material and Methods: authors searched for “uterine smooth muscle tumor of uncertain malignant potential” in PubMed and Scopus databases, from 2000 to March 2023. Pertinent articles were obtained in full-text format and screened for additional references. Only articles in English language were included. Studies including full case description of patients with histopathological diagnosis of STUMP in accordance with Stanford criteria were included. Results: The median age was 43 years old. Symptoms are similar to those of leiomyomas, with a mean diameter of 8.0 cm. Total hysterectomy with or without bilateral salpingo-oophorectomy is the standard care for women if fertility desire is satisfied. Myomectomy alone can be considered for young patients. Although these tumors have not a high malignant potential, several studies described recurrence and metastases. Conclusions: STUMPs are complex uterine smooth muscle tumors, with a rare but reasoned clinical–diagnostic management. Considering the high clinical and histological complexity of these tumors, high level of expertise is mandatory.